Pengaruh Store Atmosphere dan Brand Image terhadap Keputusan Pembelian dengan Minat Beli sebagai Variabel Intervening: Studi Empiris pada Konsumen Mixue di Yogyakarta - Henny Welsa, Henny Welsa; Agus Dwi Cahya, Agus Dwi Cahya; Nurrohmah Ikha Sawitri, Nurrohmah Ikha Sawitri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study the influence of store atmosphere and brand image on purchase decisions with purchase intention as an intervening variable among Mixue consumers in Yogyakarta. This study used a quantitative research method with a purposive sampling technique to collect 105 data points of Mixue consumers in Yogyakarta. The data were analyzed by multiple linear regression using SPSS. The results of this study reveal that: 1) store atmosphere has an impact on purchase intention, 2) brand image affect purchase intention, 3) purchase intention influence purchase decisions, 4) store atmosphere indirectly and positively affect purchase decisions through the mediation of purchase intention, 5) brand image indirectly and positively influences purchase decisions through the mediation of purchase intention. For this reason, it can be concluded that all variales in the research objective have a positive influence.